ANATOMI TUJUH JENIS KAYU DARI MALUKU UTARA (Anatomy of Seven Wood Species from North Maluku) - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Gross and anatomical fentures of seven wood species from North Maluku were observed and described for identification purposes. Fibre dimension were also measured and evaluated for their suitability for pulp and paper.The colour of wood ranges from white to brown, mostly plain without figure. Only one species has decorative figure on its surface, that is Dracontomelon sp. So it is recommended for fancy veneer of plywood or for furniture.The main anatomical features of each wood species are as folows : a) vessels are exlusively solitary and aranged in radial groups in Calophyllum inophyllum; a few vesels are radially multiple up to seven cells in Heritiera sp.; (b scalariform perforation plates present mainly in Elmerillia sp.and rarely in Horsfieldia sylvestris; c) parenchymma bands are present in Calophyllum inophyllum, Horsfieldia sylvestris and Elmerillia sp. : d) rays uniseriate in Calophyllum inophyllum; e).fiber septate in Dracontomelon sp.; f) axical intercelular canals are present in Hopea sp. and Shorea koordersii; g) oil cells in Elmerillia sp. and taniniferous tube in Horsfieldia sylvestris.Five species contain fibres with medium quality (Horsfieldia sylvestris, Dracontomelon sp., Heritiera sp., Shorea koordersii and Elmerillia sp.). other species contain fibres with poor quality.